Survivor-organisation in the search for justice and reparation: A vision from grassroots organising - Pérez-Sales, Pau (Torture Journal, 2023)
Editorial to 2023(2) issue, special section on survivor engagement in torture rehabilitation. In this editorial, Pau Pérez-Sales adds a perspective based on historical experiences of organisational processes of victims of political violence and recover some of the lessons learned as contributions to the debate.